Advanced word processing - Susie H. VanHuss (South-Western, 2008)
Advance yourself to the expert level of word processing with College Keyboarding 17E: Advanced Word Processing, Lessons 61-120. This text helps you focus on document mastery and advanced word-processing functions with Microsoft Word 2007. You'll quickly master Word's functions for business correspondence, tables, reports, and administrative and employment documents, plus, you'll learn graphics and design enhancement functions, ensuring that you have the skills you need to produce professional and appealing documents and business communications